INFECTIVE ENDOCARDITIS IN A RHEUMATOLOGIST'S PRACTICE - E Yu Ponomareva; Andrei Petrovich Rebrov (Научно-практическая ревматология, 2012)
Objective: to analyze «rheumatic» symptoms in patients with infective endocarditis (IE) and to investigate the specific features of the disease and hemodynamics in patients with prior rheumatic valvular disease Subjects and methods. The study included 184 patients with documented IE. The rate of “rheumatic” manifestations, such as joint, muscle, and skin lesions, visceral disorders, and laboratory changes, was estimated. Central hemodynamic parameters were studied in patients with IE in the presence of rheumatic heart disease. Results. Locomotor apparatus lesion was noted in 44.8% of the patients with IE, cutaneous hemorrhagic vasculitis in 18%, pericarditis in 10%, pleurisy in 19%, glomerulonephritis in 60%, leukopenia in 9%, thrombocytopenia in 32%, elevated C-reactive protein levels in 92%, circulating immune complexes in 72%. Glomerulonephritis and hemorrhagic vasculitis more frequently develop in injection drug users (p < 0.0001). Rheumatic heart disease was pre-ceded by IE in 24 patients (13% among the all patients and 27% among those with secondary IE). In the patients with secondary IE evolving in the presence of prior rheumatic heart disease, pulmonary artery systolic pressure (PASP) and cardiac arrhythmia rates were significantly higher than those in primary IE (62.5 and 53 mm Hg; p < 0.05; 62 and 32%; p < 0.025). Conclusion. The «rheumatic» manifestations were common in patients with IE and require their differential diagnosis with rheumatic diseases. Their degree correlates with systemic in-flammatory disease activity. In the patients with IE and prior rheumatic heart involvement, PASP and the frequency of arrhythmias are higher than in those with primary IE.